Multiple factors explain species‐specific regeneration of mangrove seedlings and saplings after a major hurricane - Veronica B. Restrepo; Edward Castañeda‐Moya; John S. Kominoski; Elena Solohin (Ecosphere, 2025)
Abstract Mangroves play a crucial role in mitigating hurricane impacts in coastal ecosystems, and their adaptive traits enable regeneration and forest recovery following these disturbances. Yet, how species‐specific regeneration varies across life stages and interacts with environmental conditions is poorly understood. We quantified regeneration rates of three dominant species of mangrove seedlings and saplings (Avicennia germinans, Laguncularia racemosa, and Rhizophora mangle) recovering from a major hurricane. We selected forests with varying light availability and phosphorus (P) gradients in the Everglades (Florida, USA). From 2020 to 2022, we measured biannual stem elongation, height, and density of seedlings and saplings, and collected porewater variables (salinity, sulfide, and inorganic nutrients) and continuous light intensity to assess species‐specific drivers of regeneration. Species‐specific growth rates, total height, and density varied across sites, driven by differences in porewater P and light. Growth rates of R. mangle seedlings and both R. mangle and L. racemosa saplings were influenced by light, while A. germinans growth rates were unaffected. Only R. mangle and L. racemosa saplings were influenced by porewater P, while growth of both seedlings and saplings was unaffected by porewater salinity and sulfide. Mangrove regeneration post‐disturbance is explained by spatial differences in subsidies and stressors and the composition of species and life stages, underscoring complex regeneration strategies in mixed‐species forests.